Changes in North Atlantic Oscillation drove Population Migrations and the Collapse of the Western Roman Empire - B. Lee Drake (Nature Portfolio, 2017)
Abstract Shifts in the North Atlantic Oscillation (NAO) from 1–2 to 0–1 in four episodes increased droughts on the Roman Empire’s periphery and created push factors for migrations. These climatic events are associated with the movements of the Cimbri and Teutones from 113–101 B.C., the Marcomanni and Quadi from 164 to 180 A.D., the Goths in 376 A.D., and the broad population movements of the Migration Period from 500 to 600 A.D. Weakening of the NAO in the instrumental record of the NAO have been associated with a shift to drought in the areas of origin for the Cimbri, Quadi, Visigoths, Ostrogoths, Huns, and Slavs. While other climate indices indicate deteriorating climate after 200 A.D. and cooler conditions after 500 A.D., the NAO may indicate a specific cause for the punctuated history of migrations in Late Antiquity. Periodic weakening of the NAO caused drought in the regions of origin for tribes in antiquity, and may have created a powerful push factor for human migration. While climate change is frequently considered as a threat to sustainability, its role as a conflict amplifier in history may be one of its largest impacts on populations.